From Wādī Mīzāb to Unguja, Zanzibar’s scholarly links - Sadgrove, Philip C. (2001)
This paper discusses the links, through correspondence found in the Zanzibar archives, in the late 19th and early 20th century maintained between the remote community of Wādī Mīzāb, in the person of the great Algerian Ibāḍī scholar, Muḥ. b. Yūsuf Iṭfayyish (1820/1-1914) and the Sultans of Zanzibar. The letters, in an obscure classical format, inter alia raise questions of patronage, the precarious impecunious position of scholars and problems of publishing. The paper was kindly made available to me before its publication. Sadgrove also treats al-Maṭb. al-Bārūniyya in Cairo and al-Maṭb. al-Sulṭāniyya at Zanzibar. See Custers 2006a.
Keywords: Zanzibar

From Wadi Mizab to Unguja: Zanzibar’s Scholarly Links - Sadgrove, Philip C. (The transmission of learning in Islamic Africa, 2004)
Keywords: Zanzibar